2022
DOI: 10.17582/journal.pjz/20220712070711
|View full text |Cite
|
Sign up to set email alerts
|

Epitopes Determination for OMICRON: The COVID-19 New Variant

Abstract: Authors' Contribution WN gave the idea and provided the facilities and guidance and also helped in writing the manuscript. BB collected the samples and provided the data. NQ and JG performed the experiments and wrote the manuscript. ED analyzed the data. SW helped in writing the manuscript. CG helped in experimentation. HG helped in bioinformatics analysis. HJ helped in sample collection. BR helped in figure preparation. TH helped in data analysis. All authors reviewed the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The amino acid analyses for the S2 subunit revealed that mutations N764K and N856K provide cleavage sites for SKI-1/S1P and prevent the internal fusion peptide from being exposed to the membrane fusion and syncytia formation. The protein convertase SKI-1/S1P is expressed in the bronchus and nasopharynx but not in the lungs, which may explain differing tissue tropisms [ 90 , 91 , 92 , 93 , 94 ]. Sub-variants BA.1 and BA.1.1 showed N764K and N856K mutations, whereas BA.2, group 3, and group 7 showed only N764K.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid analyses for the S2 subunit revealed that mutations N764K and N856K provide cleavage sites for SKI-1/S1P and prevent the internal fusion peptide from being exposed to the membrane fusion and syncytia formation. The protein convertase SKI-1/S1P is expressed in the bronchus and nasopharynx but not in the lungs, which may explain differing tissue tropisms [ 90 , 91 , 92 , 93 , 94 ]. Sub-variants BA.1 and BA.1.1 showed N764K and N856K mutations, whereas BA.2, group 3, and group 7 showed only N764K.…”
Section: Discussionmentioning
confidence: 99%